CpG ODN G9.1 as a novel nasal ODN adjuvant elicits complete protection from influenza virus infection without causing inflammatory immune responses. Issue 36 (23rd August 2019) - Tateishi, Koichiro; Fujihashi, Kohtaro; Yamamoto, Norio; Hasegawa, Hideki; Ainai, Akira; Sato, Kayoko; Iho, Sumiko; Yamamoto, Saburo; Maeyama, Jun-ichi; Odagiri, Takato; Asanuma, Hideki
Abstract: This study examined the protective efficacy of and immune response to a nasal influenza vaccine combined with a novel mucosal oligodeoxynucleotide (ODN) adjuvant, CpG ODN G9.1 (G9.1), in a model of infection limited to the upper respiratory tract (URT) and a model of infection in the lower respiratory tract (LRT). Mice were nasally primed with an A/California/7/2009 (Cal7) split vaccine (X179A) plus G9.1 and were then nasally given a booster with X179A alone. When mice were challenged with either a large (infection of the LRT) or small (infection limited to the URT) volume of live Cal7 influenza virus, mice nasally given G9.1 combined with X179A had a markedly higher rate of protection against infection limited to the URT. Moreover, this group of mice promptly recovered from an infection of the LRT. When mice were subcutaneously (s.c.) given X179A as a current form of vaccination, they had no protection from an infection limited to the URT but they did recover from an infection of the LRT. The patterns of protection were closely correlated with influenza virus-specific mucosal secretory IgA (SIgA) or serum IgG antibody (Ab) responses. Thus, SIgA Abs responses play an important role in protection from an infection limited to the URT while influenza virus-specific serum IgG Ab responses help to protect from an infection of the LRT. A finding of note is that lungs from mice nasally given G9.1 had low levels of type I IFN-associated protein- and transcription factor-specific mRNA expression. These results suggest that nasal G9.1 can be used as an effective and safe mucosal adjuvant for influenza vaccines since this nasal vaccine system elicits both mucosal SIgA and serum IgG Ab responses that provide complete protection without inducing potent inflammatory responses.